SYNTHESIS AND COORDINATION CHEMISTRY OF NEW SCHIFF-BASE BIS(CROWN ETHER) LIGANDS CONTAINING RECOGNITION SITES FOR ALKALI-METAL AND TRANSITION-METAL GUEST CATIONS - CRYSTAL-STRUCTURE OF A COPPER(I)-POTASSIUM COMPLEX - Beer, P; Crane, C; Drew, M (1991)
New Schiff-base bis(crown ether) ligands L1-L5 containing recognition sites for alkali- and transition-metal guest cations have been prepared by the condensation of two equivalents of 15-formyl-2,3,5,6,8,9,11,12-octahydro-1,4,7,10,13-benzopentaoxacyclopentadecine with diamines H2NXNH2 (X = [CH2]2S[CH2]2, [CH2]2S[CH2]2S[CH2] 2, [CH2]2S[CH2]3S[CH2] 2, [CH2]3S[CH2]2S[CH2] 3 or [CH2]2NH[CH2]2). The sodium cation forms 2:1 Na+:L complexes, whereas the larger potassium cation produces 1: 1 intramolecular sandwich complexes with these ligands. Homometallic copper(I) complexes and heteropolymetallic copper(I)-sodium and -potassium complexes have also been isolated. A single-crystal X-ray structure of one copper-potassium complex has been determined. Heteropolymetallic silver(I)-sodium and -potassium ligand complexes have also been prepared. Carbon-13 NMR titration studies suggest that the stoichiometry of the Schiff-base bis(crown ether) ligand to potassium guest cations is dependent upon the stereochemical requirements of the co-bound silver(I) guest cation.